The GDF11 Promotes Nerve Regeneration After Sciatic Nerve Injury in Adult Rats by Promoting Axon Growth and Inhibiting Neuronal Apoptosis - Lin, Junhao; Shi, Jie; Min, Xiang; Chen, Si; Zhao, Yunpeng; Zhang, Yuanqiang; Cheng, Lei (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Introduction: Sciatic nerve injury is a common injury of the nervous system. Stem cell-based therapies, drug-based therapies and rehabilitation physiotherapy therapies are currently available, but their limited therapeutic efficacy limits their use. Here, we aimed to explore a novel lentiviral-based gene therapeutic strategy and to elaborate its mechanism. Materials and Methods: Recombinant GDF11 protein was used for the in vitro treatment of dorsal root ganglion (DRG) cells. Lentivirus was used to construct a vector system for the in vivo expression of GDF11. The nerve conduction function was detected using action-evoked potentials at different time periods, and the regulatory effect of nerves on target organs was detected by weighing the gastrocnemius muscle. Immunofluorescence of NF200 and S100 was used to show the regeneration of the sciatic nerve, and myelin and Nissl staining were performed to observe the pathological features of the tissue. Western was used to validate signaling pathways. The expression of related genes was observed by qPCR and Western blotting, and cell apoptosis was detected by flow cytometry. Result: GDF11 promotes the axonal growth of DRG cells and inhibits DGR cell apoptosis in vitro. GDF11 acts by activating the Smad pathway. GDF11 promotes the recovery of damaged sciatic nerve function in rats, the regeneration of damaged sciatic nerves in rats, and myelin regeneration of damaged sciatic nerves in rats. GDF11 also exerts a protective effect on neuronal cells in rats. Conclusion: Based on the present study, we conclude that GDF11 promotes axonal growth and inhibits DRG cell apoptosis in vitro through the Smad pathway, and lentivirus-mediated GDF11 overexpression in vivo can promote the recovery of sciatic nerves after transection by promoting axonal growth and inhibiting neuronal apoptosis in the spinal cord.